Mangiferin: Analgesic properties in neuropathic pain, molecular docking and meta-analysis - Bo-tao Chang (Elsevier, 2022)
Aim: : To investigate the analgesic effects of mangiferin (MAF) in experimental neuropathic pain (NPP) models and underlying mechanism. Methods: : Databases including Pubmed, Web of Science, Embase, Cochrane Library, China national knowledge infrastructure (CNKI), Wangfang, and Weipu were used to search for the related studies. The search terms such as MAF, NPP, meta-analysis, rat, and mouse were used in various scientific databases. Meta-analysis was used to assay the analgesic efficacy of MAF. Further, molecular docking analysis was used to measure bindings of MAF and NPP-related proteins. Results: : 6 studies were eventually included for the meta-analysis according to the inclusion and exclusion criteria. The meta-analysis results demonstrated that MAF significantly inhibited acetic acid-induced writhing responses, formalin-induced pain behavior, thermal analgesia, and mechanical allodynia as compared with the model control. However, risk of bias especially blinding existed in the included studies. The publication bias was checked by Begg's and Egger's tests. The molecular docking analysis indicated that MAF bound to 62 pain-related proteins at different levels. The top 10 predicted target proteins of MAF were glutamate carboxypeptidase II (GCPII), dopamine transporter (DAT), N-methyl-d-aspartic acid receptor 2B (NMDAR2B), transient receptor potential member 8 (TRPM8), monoamine oxidase type B (MAO-B), sodium voltage-gated channel alpha subunit 9A (SCN9A), fatty acid amide hydrolase (FAAH), gamma-secretase (GS), angiopoietin-1 (ANGPT1), and ANGPT2 based on the scores assessed by hydrogen bonding and hydrophobic interactions. Conclusions: : In summary, MAF exerts the analgesic efficacy in the murine experimental pain models, which is associated with this compound binding to the NPP-related target proteins.